A cross sectional study on awareness regarding breaking bad news among medical interns - Subita Pranav Patil; Ulhas Gandal; Seema Sanjay Bansode-Gokhe (Al Ameen Medical College, 2017)
Background: Bad news is a situation where there is a feeling of no hope or a threat to person's mental or physical wellbeing. Disclosing bad news needs appropriate communication skills, resulting in a satisfied doctor-patient relationship. Most of the medical graduates acquire this skill through observation and not through specific training. Objectives: To study awareness regarding breaking bad news among medical interns. Methods: This cross sectional study was conducted among complete batch of 112 medical interns, attached to a tertiary care hospital between Jan-June 2016. A predesigned, pretested, semi- structured questionnaire was used. Results: Only 58% of the participants were aware about what is a bad news but 80% were not aware about how to break a bad news. Half of them felt no need to conduct training. Over >3/4th agreed that doctors were primary deliverers and it can cause stress, anxiety in the recipient. 95% felt that it can alter patients view if conducted improperly. 3/4th could not disclose comfortably, accepting need of specific training for the same. Discussing end-of-life issue was most difficult (48%). Conclusion: Formal training during internship can result in good communication skills, improved doctor-patient relationship and can achieve enhanced quality of services.